Numerical analysis of energy loss characteristics of guide vane centrifugal pump as turbine - Wang, Ziqiang; Wang, Wenjing; Wang, Dongxu; Song, Ying (Frontiers in Energy Research, 2024)
The structure of the guide vane centrifugal pump as turbine is complex, and the internal flow characteristics directly affect the energy loss distribution. The numerical method and entropy generation theory are used to analyze the energy loss distribution of each flow component of the guide vane centrifugal pump as turbine at different flow conditions. And the transient fluctuation law of hydraulic loss of passage component is also studied. The results show that the loss in the impeller accounts for 54%–58% under small flow conditions, and the loss in the guide vane accounts for 50%–61% under large flow conditions. The hydraulic loss of the impeller and guide vane is affected by the interaction between the impeller and guide vane, volute. And there are five obvious peaks and troughs in the 1/6 period. The primary and secondary frequencies of impeller hydraulic loss change with the flow rate. At the 0.57QBEP condition, the primary and secondary frequency of the impeller loss is blade frequency and 5 times blade frequency respectively, while the frequencies under the condition of 1.43QBEP are opposite. The primary and secondary frequencies of guide vane hydraulic loss are different under different flow conditions. The hydraulic loss of volute is mainly affected by the interference between the impeller and volute under various flow conditions, and the primary frequency is blade frequency.